"Small town" entrepreneurial ecosystems: Implications for developed and emerging economies. Issue 3 (4th September 2017) - Roundy, Philip T.
Abstract : Purpose: Entrepreneurial ecosystems are receiving growing attention from scholars, practitioners and policy-makers in both developed and developing countries. Studies of this phenomenon have focused almost exclusively on ecosystems in large, urbanized regions and metropolitan areas, located primarily in developed economies. However, the prevalence of small cities across the globe and the increasing acknowledgment that entrepreneurship in small towns is a key determinant of their economic development and rejuvenation suggests that entrepreneurial ecosystems research would benefit from a broader lens of inquiry. Thus, the purpose of this paper is to introduce a framework for studying entrepreneurial ecosystems in small towns. Design/methodology/approach: This conceptual paper introduces the concept of small town entrepreneurial ecosystems (STEEs), draws from a wide-ranging set of disciplines to delineate the ways in which small town ecosystems are similar to and different than their larger counterparts and theorizes about several strategies STEEs use to overcome their limitations. Findings: It is theorized that entrepreneurship in small cities is best conceptualized as the outcome of an ecosystem, which means that although small towns may not have some of the same key components as entrepreneurial ecosystems in large urban centers, other elements of the ecosystem may be able to bolster these deficiencies. It also suggests that those attempting to create or develop small town ecosystems may need to be entrepreneurial in the way they attract, view and utilize resources. Finally, it is theorized that small cities may be able to engage in several strategies to overcome their limitations and create vibrant entrepreneurial communities. Originality/value: The theory developed produces implications for scholars focused on entrepreneurial ecosystems, economic development and emerging economies and suggests practical implications for policy-makers and development organizations seeking to improve the economic landscape of small cities.